Impedance Model of a Water-Filled Pt Nanopore: Interfacial Charging and Chemisorption Effects. Issue 6 (14th April 2020) - Sun, Ying; Eikerling, Michael; Zhang, Jianbo; Huang, Jun
Abstract : The impedance response contains rich information about an electrochemical system under investigation. Disentangling this highly convoluted information requires physical models. In this work, we develop a theoretical impedance model for a water-filled Pt nanopore, as a representative element in electrocatalytically active layers of polymer electrolyte fuel cells or electrolysis cells. The model accounts for double-layer charging, proton conduction and oxygen transport in the pore as well as chemisorption and oxygen reduction reaction at the Pt surface. It relaxes two widely used assumptions, namely, electroneutrality in solution phase and infinitely fast adsorption kinetics. Analytical impedance expressions are obtained for different limiting cases and impedance fingerprints of interfacial charging and chemisorption effects are identified.